Non-phosphorylatable mutants of Ser184 lead to incomplete activation of Bax - Simonyan, Lilit; Gonin, Mathilde; Hanks, James; Friedlein, Jordan; Dutrec, Kevin; Arokium, Hubert; Rouchidane Eyitayo, Akandé; Doudy, Toukounou Megann; Chaignepain, Stéphane; Manon, Stéphen; Dejean, Laurent (Frontiers in Oncology, 2023)
The S184 residue of Bax is the target of several protein kinases regulating cell fate, including AKT. It is well-established that, in cellulo, the substitution of S184 by a non-phosphorylatable residue stimulates both the mitochondrial localization of Bax, cytochrome c release, and apoptosis. However, in in vitro experiments, substituted mutants did not exhibit any increase in their binding capacity to isolated mitochondria or liposomes. In spite of exhibiting a significant increase of the 6A7 epitope exposure, substituted mutants remain limited in their ability to form large oligomers, suggesting that they high capacity to promote apoptosis in cells was more related to a high content than to an increased ability to form large pores in the outer mitochondrial membranes.